2013
DOI: 10.1105/tpc.112.106377
|View full text |Cite
|
Sign up to set email alerts
|

AUREOCHROME1a-Mediated Induction of the Diatom-Specific Cyclin dsCYC2 Controls the Onset of Cell Division in Diatoms (Phaeodactylum tricornutum)

Abstract: Cell division in photosynthetic organisms is tightly regulated by light. Although the light dependency of the onset of the cell cycle has been well characterized in various phototrophs, little is known about the cellular signaling cascades connecting light perception to cell cycle activation and progression. Here, we demonstrate that diatom-specific cyclin 2 (dsCYC2) in Phaeodactylum tricornutum displays a transcriptional peak within 15 min after light exposure, long before the onset of cell division. The prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
142
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(149 citation statements)
references
References 73 publications
4
142
2
1
Order By: Relevance
“…through light sensors such as AUREOCHROME) and indirectly through metabolic shifts, internal pH shifts, and redox. In diatoms, the most well resolved regulators of cell cycle progression are light‐sensitive proteins (Huysman et al ., 2013, 2014). In this study, there are similarly choreographed changes to the T. pseudonana transcriptome, but under continuous light conditions, illustrating the existence of other regulators that control coexpression modules besides light fluctuations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…through light sensors such as AUREOCHROME) and indirectly through metabolic shifts, internal pH shifts, and redox. In diatoms, the most well resolved regulators of cell cycle progression are light‐sensitive proteins (Huysman et al ., 2013, 2014). In this study, there are similarly choreographed changes to the T. pseudonana transcriptome, but under continuous light conditions, illustrating the existence of other regulators that control coexpression modules besides light fluctuations.…”
Section: Discussionmentioning
confidence: 99%
“…Genes such as LHCX1 and AUREOCHROME 1‐a in Phaeodactylum tricornutum are known to be light‐responsive (Bailleul et al ., 2010; Costa et al ., 2013). In the case of AUREOCHROME 1‐a, the specific mechanism by which light regulates cell division through the activity of dsCYC2 (a diatom‐specific cyclin) has been elucidated (Huysman et al ., 2013). Alternatively, recent functional genomics studies in diatoms and other microalgae have shown that transcription of large suites of genes is coordinated with growth‐related processes such as chloroplast division, release from nitrogen and silicon starvation, cell wall synthesis, onset of cell division, and circadian shifts, suggesting that many genes may be under the control of master regulators (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Schellenberger Costa et al (35) suggested that aureochrome 1a is involved in photoacclimination. Furthermore, Huysman et al (36) reported that it mediates induction of diatom-specific cyclin dsCYC2 and controls the onset of cell division, and suggested that it functions synergistically with the bZIP transcription factor bZIP10 to induce dsCYC2 transcription. In other organisms, it has been postulated that overexpression of NgAUREO1, the gene coding for aureochrome 1 from Nannochloropsis gaditana, in Saccharomyces, leads to an increase of lipid accumulation in yeast cells (37).…”
Section: Discussionmentioning
confidence: 99%
“…For gene expression studies, cells were specifically illuminated for 30 min at low irradiance (5 mE$m 22 $s 21 ) with a series of narrow-spectrum LED light sources (l max : 660, 688, 732, 740, or 765 nm, and half-bandwidth below 17 nm for all the wavelengths). DCMU treatment was performed as described (Huysman et al, 2013). All the experiments were done with cells in exponential phase of growth (1 to 2$10 6 cells/mL).…”
Section: Culture Conditionsmentioning
confidence: 99%
“…Total RNA was extracted as described (Huysman et al, 2013). For RTqPCR, 500 ng of total RNA was reverse-transcribed using the QuantiTect reverse transcription kit (Qiagen) and the reaction accomplished with 12.5 ng cDNA as template, following the SsoAdvanced Universal SYBR Green Supermix instructions (Bio-Rad), in a CFX 96 real-time detection system (Bio-Rad).…”
Section: Rna Extraction and Gene Expression Analysismentioning
confidence: 99%